2021
DOI: 10.3390/brainsci11091114
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Theta Burst Stimulation to the Primary Motor Cortex Reduces Cortical Inhibition: A TMS-EEG Study

Abstract: Introduction: The aim of this study was to reveal the effects of intermittent theta burst stimulation (iTBS) in modulating cortical networks using transcranial magnetic stimulation and electroencephalography (TMS-EEG) recording. Methods: Eighteen young adults participated in our study and received iTBS to the primary motor cortex (M1), supplementary motor area, and the primary visual cortex in three separate sessions. A finger tapping task and ipsilateral single-pulse TMS-EEG recording for the M1 were administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 62 publications
3
24
0
Order By: Relevance
“…In the time domain, we did not observe any significant change in LMFP or GMFP after iTBS. Several studies have investigated acute adaptations in LMFP and GMFP after iTBS applied on M1 in healthy adults, but the results lack a common thread ( Gedankien et al, 2017 ; Bai et al, 2021 ; Ozdemir et al, 2021 ). No significant change in LMFP or GMFP after iTBS was observed in some studies ( Gedankien et al, 2017 ; Ozdemir et al, 2021 ), but a reduction in GMFP after iTBS was reported in a recent study ( Bai et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the time domain, we did not observe any significant change in LMFP or GMFP after iTBS. Several studies have investigated acute adaptations in LMFP and GMFP after iTBS applied on M1 in healthy adults, but the results lack a common thread ( Gedankien et al, 2017 ; Bai et al, 2021 ; Ozdemir et al, 2021 ). No significant change in LMFP or GMFP after iTBS was observed in some studies ( Gedankien et al, 2017 ; Ozdemir et al, 2021 ), but a reduction in GMFP after iTBS was reported in a recent study ( Bai et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As TEP main peaks are not always present in stroke survivors, LMFP and GMFP have the advantage of quantifying TEPs in stroke studies ( Tscherpel et al, 2020 ). The acute adaptations in LMFP and GMFP after iTBS have been investigated in healthy adults, but results remain inconsistent in current literature ( Gedankien et al, 2017 ; Bai et al, 2021 ; Ozdemir et al, 2021 ). Some studies reported no change in LMFP or GMFP after iTBS ( Gedankien et al, 2017 ; Ozdemir et al, 2021 ), while one study reported reduced GMFP after iTBS ( Bai et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations